Differentiating acute fatigue and overreaching during intensified training using a recursive least squares algorithm combined with the variable dose-response model - Busso, T.; Chalencon, S. (European Journal of Applied Physiology, 2025)
Purpose This study aimed to investigate whether the variable dose-response model, with estimates free to vary over time, can account for overreaching during intensified training in swimmers.